Transmission of Diphyllobothrium ditremum to Arctic Char ( Salvelinus alpinus ) in Two Subarctic Quebec lakes - Bérubé, Michel; Curtis, Mark A. (Canadian Journal of Fisheries and Aquatic Sciences, 1986)
Diphyllobothrium ditremum (Cestoda: Pseudophyllidea) transmission to arctic char (Salvelinus alpinus) was investigated at two small (<10 ha) lakes in northern Quebec, where the char populations exhibit a marked difference in plerocercoid prevalence (78 vs. 18%) and abundance (27.7 vs. 1.2 plerocercoids/fish). The highly infected char population was characterized by slow growth and poor feeding conditions. Feeding behavior of char in the two lakes differed principally in the fall, when consumption of benthos significantly decreased in the highly infected population as char fed more on copepods or sticklebacks (Gasterosteus aculeatus). Presence of these two food items in char stomachs was associated with high abundance of D. ditremum. The availability of alternative foods, such as larval insects and amphipods, appears to prevent char from acquiring heavy infections of D. ditremum, even in circumstances where all potential hosts are present.